PERSEPSI SISWA TERHADAP PENERAPAN MODEL KOOPERATIF TIPE THINK PAIR SHARE (TPS) PADA PEMBELAJARAN IPA BIOLOGI DI KELAS VII. 4 SMP NEGERI 2 TAMBANG - Elsha Sherin Fabiola; Arnentis '; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstracts: The descriptive research has conducted to determine students perceptions VII.4 grade SMPN 2 Tambang of the application of cooperative models of TPS (Think Pair Share) in science teaching Biology Academic Year 2015/2016. The research was conducted in SMP Negeri 2 Tambang. This research was held in April and May 2016. The sample was grader VII.4 totaling 20 students. This study begins with the first made the implementation of cooperative model TPS to students. After Biology learning with the implementation of TPS type cooperative model is completed, a questionnaire distributed to 20 students. The questionnaire distributed contains 30 statements using five indicators which are attention, expectations, needs, system of values, and personality type. The type of questionnaire used was a enclosed questionnaire. The number of items prepared in accordance with the need to be able to represent the students perception of learning strategies and biology for students perception of the implementation of learning model TPS. Then data tabulated based on answers to the questionnaire of each item is given a score, for the items in question consists of five alternatives. Answers were analyzed using a graduated scale (rating scale) by using a value-shaped figure results. The average perception of students towards science biology teaching after implementation of cooperative model tps at each indicator in a row is 4.51 (Good), 4.53 (Good), 4.7 (Very Good), 4.6 (Good), 4.66 (Good). The results showed that the students perception of the implementation of the cooperative model TPS in science teaching Biology is good with average 4.6.Keywords: Descriptive, cooperative model of think pair share, biology